What price to pay? The trade-off between independence and influence in European regulation. (July 2021) - Ruffing, Eva
This article asks whether the strengthened, institutionalised role that some European agencies play in delegated decision-making endangers their actual independence. In some particular sensitive policy domains, such as pharmaceuticals security, financial markets and energy, European agencies exist which are formal agenda-setters in delegated decision-making, meaning that the European Commission can either accept or reject their proposals but is hardly allowed to change them. These procedures were established to guarantee particularly expert-based decision-making. However, the article argues that under these conditions, the Commission will be eager to interfere with the agencies' proposal preparation to ensure that the proposal is in line with its position, thereby weakening the de facto independence of agencies. Such procedures come, therefore, with unexpected effects in practice. However, the article demonstrates that these effects vary with organisational resources on the agencies' and the Commission' side and the expected constraining effects of the decisions taken.